2022
DOI: 10.1038/s41420-022-01250-8
|View full text |Cite
|
Sign up to set email alerts
|

RACK1 is evolutionary conserved in satellite stem cell activation and adult skeletal muscle regeneration

Abstract: Skeletal muscle growth and regeneration involves the activity of resident adult stem cells, namely satellite cells (SC). Despite numerous mechanisms have been described, different signals are emerging as relevant in SC homeostasis. Here we demonstrated that the Receptor for Activated C-Kinase 1 (RACK1) is important in SC function. RACK1 was expressed transiently in the skeletal muscle of post-natal mice, being abundant in the early phase of muscle growth and almost disappearing in adult mature fibers. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
(123 reference statements)
0
1
0
Order By: Relevance
“…Besides, these layers act as supporting basal lamina for the maintenance of muscle progenitor cells, namely satellite cells [3]. It is suggested that satellite cells are involved in muscle regeneration in response to several insulting conditions, leading these cells to exit from quiescent status, enter proliferation, and subsequently differentiate into mature myocytes [4]. Despite the regenerative potential of satellite cells, extensive and bulk injuries to the muscle mass lead to abnormal extracellular matrix (ECM) production, and fibrotic changes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, these layers act as supporting basal lamina for the maintenance of muscle progenitor cells, namely satellite cells [3]. It is suggested that satellite cells are involved in muscle regeneration in response to several insulting conditions, leading these cells to exit from quiescent status, enter proliferation, and subsequently differentiate into mature myocytes [4]. Despite the regenerative potential of satellite cells, extensive and bulk injuries to the muscle mass lead to abnormal extracellular matrix (ECM) production, and fibrotic changes [5].…”
Section: Introductionmentioning
confidence: 99%